Ultrafast green synthesis of silver nanoparticles as fluorescent nanosensors for determination of isoniazid and nitrofurantoin in biological fluids and pharmaceuticals - Galal Magdy; Eman Aboelkassim; Fathalla Belal (Scientific Reports)
Abstract The current study presents a green, straightforward, and ultrafast microwave-assisted method for the synthesis of Ag-NPs in only 40 s, using the Paeonia officinalis root extract as a reducing agent, for the first time. Characterization of the produced Ag-NPs was carried out using different spectroscopic and microscopic methods. They exhibited strong emission peak at 318 nm following excitation at 227 nm. The developed Ag-NPs were utilized as a green fluorescent nanosensor for determination of isoniazid (ISN) and nitrofurantoin sodium (NIF). The native fluorescence of Ag-NPs was observed to be quantitatively quenched by the studied drugs. Validation of the method exhibited linear relationship for ISN and NIF in the range of 20.0-100.0 µM and 10.0–60.0 µM with detection limits of 1.12 µM and 0.98 µM, respectively. Due to the high selectivity and sensitivity, the suggested method was also applied for ISN and NIF estimation in biological fluid samples and pharmaceutical formulations with acceptable % RSD and % recoveries. Assessment of the Ag-NPs’ antimicrobial activity was performed, and the synthesized Ag-NPs showed noteworthy antimicrobial activities. The evaluation of the method’s eco-friendliness and greenness was also performed using AGREE and ComplexGAPI metrics. ICHQ2 (R2) guidelines were followed to validate the developed method.